Artificial Intelligence as a Tool for Strengthening Pesantren Education in the Digital Era - Ari Fajar Santoso; Basel Abdulwahab; Ruchdee Sannakit (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2026)
The rapid development of artificial intelligence (AI) is transforming educational practices across the globe. Islamic boarding schools (pesantren), one of the oldest and most influential educational institutions in Indonesia, are increasingly encountering the opportunities and challenges presented by AI technologies. Traditionally rooted in classical Islamic scholarship, character formation, and community-based learning, pesantren education faces the task of integrating digital technologies without losing its core values. This article examines how AI can function as a tool for strengthening pesantren education in the digital era. Using a conceptual and literature-based approach, the study explores three major dimensions: AI-assisted learning for religious knowledge, the transformation of pedagogical practices, and the ethical governance of AI in Islamic educational environments. The findings suggest that AI has the potential to enhance access to classical Islamic texts, support Arabic language learning, and facilitate personalized learning for santri. At the same time, careful ethical guidance and pedagogical supervision are required to ensure that AI complements rather than replaces traditional learning methods such as talaqqi and halaqah. The article proposes a conceptual framework illustrating the integration of AI tools with pesantren values, emphasizing the central role of teachers and moral guidance. The study contributes to emerging discussions on the future of Islamic education in the age of intelligent technologies and offers insights for policymakers, educators, and pesantren leaders seeking to adopt AI responsibly.